Book Review: Una mirada histórica al bienestar rural argentino. Debates y propuestas de análisis, by Alejandra de Arce and Alejandra Salomón (compilers) - Rossi, Ignacio Andrés (2021)
A recently published book produced by the Center for Studies of Rural Argentina of the National University of Quilmes (UNQ), Argentina, is discussed. This text contains a set of social studies of rural Argentina faced from multiple disciplinary perspectives: state formations and their impact on social evolution, the role of schools and health in peri-urban spaces, housing and industries in the economies regional, among others. The proposal becomes enriching for Latin American rural spaces as different theoretical and methodological tools are offered that can contribute to the development of this type of analysis in the region. The understanding of spaces and social problems becomes a fundamental tool to think about long-term solutions after the rural transformations developed in the last quarter of the century. The social sciences play a major role in this endeavor.